Evaluasi Kinerja Klinik Sanitasi Puskesmas: Analisis Perencanaan Intervensi Lingkungan Dalam Pengendalian Vektor Penyakit Menular - Injilita Rutemia Donsu; Meylita Injilia Kodongan; Chelvin Irgil Momongan; Karunia Kaligis; Eunike Febryca Br Keliat; Gita Maelkia Situmorang; Suhardi Ibrahim; Augustinus Robin Butarbutar (STIKES Columbia Asia Medan, 2026)
Vector-borne infectious diseases remain a public health concern, particularly in tropical regions such as Indonesia. Sanitation clinics at public health centers (Puskesmas) play a role in identifying environmental risk factors and planning interventions to support vector-borne disease control. This study aimed to evaluate the performance of sanitation clinics in environmental intervention planning. The method used was a literature review of scientific articles, journals, and related documents published between 2015-2025. Data were analyzed descriptively to identify forms of environmental interventions and their effectiveness. The results showed that sanitation clinics play an important role in environmental health counseling, sanitation inspections, health education, and environmental intervention planning. However, their implementation still faces challenges, including limited numbers of sanitarians, inadequate facilities and infrastructure, and suboptimal environmental interventions. Nevertheless, sanitation clinics continue to contribute to the prevention of environment-based diseases and vector control. Therefore, strengthening resources and improving the quality of intervention planning are necessary to enhance the effectiveness of sanitation clinic programs.